2017
DOI: 10.1016/j.carbon.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of two-dimensional materials inside carbon nanotubes: Towards an enhanced synthesis of single-layered metal halides

Abstract: The unique properties of two-dimensional (2D) nanomaterials make them highly attractive for a wide range of applications. As a consequence, several top-down and bottom up approaches are being explored to isolate or synthesize single-layers of 2D materials in a reliable manner. Here we report on the synthesis of individual layers of several 2D van der Waals solids, namely CeI3, CeCl3, TbCl3 and ZnI2 by templateassisted growth using carbon nanotubes as directing agents, thus proving the versatility of this appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
2
25
1
Order By: Relevance
“…45,46 A higher amount of single-walled nanotubes within CNTs has been recently reported upon increasing the temperature of annealing, from 21.4 % at 475 ºC to 64.9 % at 1000 ºC, for the van der Waals solid ZnI 2 . 18 Nevertheless, not only the production yield is still lower than the one reported here (for PbI 2 using laser) but also much longer tubular structures are obtained by laser irradiation.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…45,46 A higher amount of single-walled nanotubes within CNTs has been recently reported upon increasing the temperature of annealing, from 21.4 % at 475 ºC to 64.9 % at 1000 ºC, for the van der Waals solid ZnI 2 . 18 Nevertheless, not only the production yield is still lower than the one reported here (for PbI 2 using laser) but also much longer tubular structures are obtained by laser irradiation.…”
Section: Resultscontrasting
confidence: 60%
“…17 The synthetic strategy proved to be versatile but requires the use of high temperatures for prolonged periods of time. Furthermore, even under the best synthetic conditions, a large fraction (at least 35 %) of other nanostructures are formed in the interior of the carbon nanotubes 18 which could strongly influence the properties. Here we present an ultrafast, energy efficient and easily scalable approach that allows the selective synthesis of single-walled lead iodide nanotubes coating the inner walls of carbon nanotubes, thus forming cylindrical van der Waals heterostructures.…”
mentioning
confidence: 99%
“…7 (a-b)). 68,[70][71][72] This solvent-free high temperature approach was based on the use of the inner cavities of CNTs as hosting templates. Thus, the growth of lead diiodide single wall nanotubes (SWNTs), with diameters ranging from 3.5 to 7.5 nm, as well as nanowires, were reported, see Fig.…”
Section: Templatingmentioning
confidence: 99%
“…A large variety of materials have been shown to also coat the inner cavities of MWCNT forming single-layered inorganic nanotubes (SLINTs), namely PbI 2 [57,58], ZnI 2 [58,59], CeCl 3 [59], CeI 3 [59], TbCl 3 [59], GdCl 3 [29], SmCl 3 [29], BiI 3 [60], GdI 3 [61] and BiCl 3 [62]. The role that the temperature of treatment has on the grown nanostructures was investigated using ZnI 2 and MWCNTs [59]. It was observed that the formation of SLINTs could be favored by increasing the temperature of treatments, reaching a selectivity of ca.…”
Section: Selected Examples Of Confined Na Nocrystalsmentioning
confidence: 99%